The epigenetic enzyme DOT1L orchestrates vascular smooth muscle cell–monocyte crosstalk and protects against atherosclerosis via the NF-κB pathway. (16th March 2022) - Farina, Floriana Maria; Serio, Simone; Hall, Ignacio Fernando; Zani, Stefania; Cassanmagnago, Giada Andrea; Climent, Montserrat; Civilini, Efrem; Condorelli, Gianluigi; Quintavalle, Manuela; Elia, Leonardo
Abstract: Aims: Histone H3 dimethylation at lysine 79 is a key epigenetic mark uniquely induced by methyltransferase disruptor of telomeric silencing 1-like (DOT1L). We aimed to determine whether DOT1L modulates vascular smooth muscle cell (VSMC) phenotype and how it might affect atherosclerosis in vitro and in vivo, unravelling the related mechanism. Methods and results: Gene expression screening of VSMCs stimulated with the BB isoform of platelet-derived growth factor led us to identify Dot1l as an early up-regulated epigenetic factor. Mouse and human atherosclerotic lesions were assessed for Dot1l expression, which resulted specifically localized in the VSMC compartment. The relevance of Dot1l to atherosclerosis pathogenesis was assessed through deletion of its gene in the VSMCs via an inducible, tissue-specific knock-out mouse model crossed with the ApoE −/− high-fat diet model of atherosclerosis. We found that the inactivation of Dot1l significantly reduced the progression of the disease. By combining RNA- and H3K79me2-chromatin immunoprecipitation-sequencing, we found that DOT1L and its induced H3K79me2 mark directly regulate the transcription of Nf-κB-1 and -2, master modulators of inflammation, which in turn induce the expression of CCL5 and CXCL10, cytokines fundamentally involved in atherosclerosis development. Finally, a correlation between coronary artery disease and genetic variations in the DOT1L gene was found because specific polymorphisms are associated with increased mRNA expression. Conclusion: DOT1L plays a key role in the epigenetic control of VSMC gene expression, leading to atherosclerosis development. Results identify DOT1L as a potential therapeutic target for vascular diseases. Structured Graphical Abstract: Structured Graphical Abstract Schematic representation of DOT1L involvement in VSMC-driven inflammation during atherosclerosis progression. DOT1L increased activity, through its H3K79me2 mark, induces the transcription of the Nf-kB genes, leading to a pro-inflammatory phenotype of VSMCs, characterized by a higher chemokine release (e.g. CCL5, CXCL10). Thus, in a model of atherosclerosis (16 weeks HFD administration), in vivo genetic deletion of DOT1L modulates the vascular inflammatory environment and protects against plaque progression. VSMC, vascular smooth muscle cell; DOT1L, disrupter of telomere silencing 1-Like; CCL5, chemokine (C-C motif) ligand 5; CXCL10, C-X-C motif chemokine ligand 10; HFD, high fat diet.